The effects of clove seed (Syzygium aromaticum) dietary administration on carcass characteristics, meat quality, and sensory attributes of broiler chickens - Suliman, Gamaleldin M.; Alowaimer, Abdullah N.; Al-Mufarrej, Saud I.; Hussein, Elsayed O.S.; Fazea, Esam H.; Naiel, Mohammed A.E.; Alhotan, Rashed A.; Swelum, Ayman A. (Poultry science, 2021)
Previous studies have shown positive outcomes associated with the incorporation of cloves into broiler chicken diets. This study aimed to evaluate carcass characteristics, meat quality, and sensory attributes of broiler chickens fed diets supplemented with different clove seed levels. A total of 240 day-old Ross 308 broiler chicks were fed 1 of seven dietary treatments. The control group diet contained 0% clove seeds, whereas the treatment group diets contained up to 6% clove seeds. The chickens' final BW was significantly different between the treatments, which decreased linearly with increasing levels of clove seed inclusion. Broiler chickens fortified with clove seeds did not significantly affect the chickens' carcass characteristics and body composition. However, an increment in weights of carcass components (liver, heart, and gizzard) was observed in low clove seed levels. In addition, water-holding capacity, cooking loss percentages, and tenderness of the meat were improved owing to clove seed inclusion (1 or 2%) compared with the control group. Further studies are warranted to optimize the outstanding use of cloves toward broiler chicken performance enhancement and to produce a high quality of meat.